Menengok Ruang Terlarang Bagi Laki-Laki: Peeking Into A Room Forbidden To Men - Siti Habibah Jazila (An-Nisa’ Journal of Gender Studies, 2009)
Simply put, if we identify all the household chores that are done from the moment we wake up until we go back to sleep, and who does them, the result is that almost all of them are done by women. This experience illustrates how, until now, all household matters seem to be the sole responsibility of women, and how the domestic sphere is considered the authoritative domain of women. This space then seems to be the sole domain of women. This experience illustrates how, for so long, all household matters have seemed to be the sole responsibility of women, how the domestic sphere has been considered the domain of women. This space then seems to be off-limits, tightly closed to men, just as the public sphere has not been widely open to women. Dengan sangat sederhana, apabila kita mengidentifikasi semua pekerjaan rumah yang dilakukan dari mulai bangun tidur hingga tidur lagi dan siapa yang mengerjakannya. Hasilnya, hampir semuanya dilakukan oleh perempuan. Pengalaman tersebut menggambarkan betapa selama ini segala urusan dalam rumah seolah-olah menjadi tanggung jawab perempuan saja, betapa wilayah domestik dianggap sebagai wilayah otoritatif perempuan. Ruang ini kemudian seolah-olah terlarang, tertutup rapat bagi kaum laki-laki sebagaimana ruang publik juga belum terbuka lebar bagi perempuan.